(untitled) (Journal of Chittagong Medical College Teachers’ Association, 2025)
Background: For Unruptured Ectopic Pregnancy (UEP) medical treatment with Methotrexate (MTX) is a safe and efficient alternative that carries none of the dangers of surgery. The aim of this study was to evaluate the outcome of medical management of ectopic pregnancy by methotrexate. Materials and methods: This cohort study was conducted in the Department of Obstetrics and Gynaecology of Chittagong Medical College Hospital (CMCH) Chattogram, Bangladesh from January 2022 to June 2022. A total of 48 admitted women with ectopic pregnancy were included in this study. The percentage of drop in b- hCG readings between days 4 and 7 was used to assess the effectiveness of medical care with methotrexate; these values had to be > 15% negative without the need for additional surgery. Collected data were classified, coded and entered into the computer for statistical analysis by using SPSS version 23. Results: The overall success rate of treatment with MTX was 97.9% and failure was 2.1%. Mean b-hCG was significantly decrease (p=0.001) when compared on admission with day 7.H/O PID was significantly higher in failed show than successful one. The successful treatment group had a considerably lower mean -hcg level in several follow-up measurements compared to the failure group (p<0.05). Conclusion: In conclusion, women with ectopic pregnancies have a safer, more successful and better option in Methotrexate (MTX) medication. JCMCTA 2024 ; 35 (2) : 49-53